Chiral 1d Metal-Organic Materials Based on Cu(Ii) and Amino Acid Schiff Bases - Venegas-Yazigi, D; Venegas-Yazigi, D (American Chemical Society, 2022)
Four new chiral coordination polymers (CPs), {[Cu(HLn)MeOH]·NO3}∞ (n = 1–4), were obtained using a chiral building block synthesized from the condensation reaction of l- or d-valine with an imidazole aldehyde. These CPs crystallize in a noncentrosymmetric space group P212121, evidencing that the chirality of the α-amino acid valine is transferred to the structure of the coordination polymer. Moreover, the CPs present a 1D structure with a Cu(II) cation in a square base pyramid geometry formed by two units of chiral ligand and a methanol molecule. The magnetic measurement and theoretical calculations show that the Cu(II) spin carriers are magnetically communicated through the carboxylate bridge, presenting a 1D ferromagnetic chain behavior. Furthermore, four new stable molecular compounds [Cu(HLn)DMSO]+ (n = 1–4), sharing the same chiral building block of CPs, were characterized by circular dichroism (CD). The theoretical electronic excited states of the molecular compounds reproduce the CD experimental spectra showing that the intrinsic chiral activity of the α-amino acid Schiff base is transferred to the Cu(II) centers. Remarkably, using crystal engineering tools, a family of chiral coordination compounds was obtained and analyzed combining several experimental and theoretical approaches, leading to a robust understanding of its chemical and physical properties. © 2021 American Chemical Society